Pelatihan Penulisan Artikel Ilmiah bagi Guru-Guru MGMP Bahasa Indonesia SMP se-Kota Pekanbaru - Alber Alber; Erni Erni; Rika Ningsih; Hermaliza Hermaliza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The implementation of this community service departs from the many complaints of teachers who have difficulty in writing scientific articles. In fact, research activities and writing scientific articles are required to be carried out by teachers in order to improve the pedagogic quality of educators. Based on this, this service needs to be carried out seriously to the stage of writing scientific articles and publishing them. Law Number 14 of 2005 concerning teachers and lecturers states firmly that teachers are required to have academic qualifications, competencies, educator certificates, and so on. With the productiveness of teachers carrying out scientific article writing activities, they can increase teacher professionalism, increase teacher competence, increase teacher confidence, and enable teachers to actively develop their knowledge and skills. The results of PkM, community service participants, in this case Indonesian junior high school MGMP teachers throughout Pekanbaru City, can understand, write scientific articles, and are able to publish their articles in reputable journals.